HOW DO INDONESIAN LAWS AND REGULATIONS SHAPE THE POLITICAL LANDSCAPE OF FORESTRY LICENSING? - Hartati; Qurochman, Taufik; Helmi; Diar, Adithiya (Faculty of Law, Universitas Pasundan, 2024)
This research aims to analyze the evolution of forestry licensing regulations before and after the enactment of the Job Creation Law (CK Law). Utilizing a normative juridical approach, this study examines conceptual, statutory, and historical aspects of forestry law. The findings reveal that the politics surrounding forestry law significantly impact the balance between investment-driven economic interests and the preservation of sustainable forest cover. Prior regulatory issues in forest management remain unaddressed by the CK Law, which primarily emphasizes the exploitation of forest resources. This focus could exacerbate carbon emissions as forest utilization investments increase. While the changes introduced by the CK Law are designed to boost investment by simplifying licensing procedures, permitting multi-business activities, and facilitating foreign investment, they also present challenges for natural resource management. The revisions dilute commitments to forest conservation, reinforce disparities in forest product utilization between large corporations and local communities, and marginalize traditional forest-dependent populations. The novelty of this research lies in its critical examination of how legal reforms aimed at economic growth may unintentionally undermine long-term environmental sustainability and social equity. The urgency of this issue is highlighted by the potential long-term consequences of these legal changes on both environmental health and community welfare. This study contributes to the broader discourse on balancing economic development with environmental protection in Indonesia’s forestry sector.